Chemistry of Natural Dyes of Batik Crafts Colouring Process. Issue 1 (June 2020) - Wahyuningsih, S; Rahmawati,; Handayani, S R; Setyaningsih,; Ponimah,
Abstract: By Fixation technique, we found the increasing stability of natural color. The aim of the study was to evaluate the performance of dyes anthocyanin, mangiferin, curcuma longa, Indigi fera and tannin (tingi) in batik dyeing. The medium was optimized by conditioning of natural dyes from amount quantity of extracted dyes in several condition: acid condition, base condition and also complexation during fixation process usually done in Batik dyeing. It was concluded that the color values were found to be influenced by the addition of namely mordants as complexation agent, consequently different fashion hues were obtained from the same dye extract using different mordants. The chemistry aspect such as an absorption in UV Visible region of each dyes and Infra Red absorption have been studied, and also a typical of fixation model should be noticed as a chemistry of dyes.